Concept and Model of Local Self-Government Using Organizational Design and Public Communications - LUKIYANOVA, Marina N.; NIKITSKAYA, Elena F.; SEDOVA, Nadezhda V. (Journal of Advanced Research in Law and Economics; Vol 8 No 3 (2017): JARLE Volume VIII Issue 3(25) Summer 2017, 2017)
The topicality of the research is development of a model that will improve the system of local self-government. The goal of the Article is to show how the introduction of elements that separate us from the strong local self-government, existing in developed countries, has an impact on results of management of the municipal structures. The local self-government was proclaimed in Russia relatively recently. But in fact, the mechanisms of its implementation have not been developed, therefore, the activities of the authorities is ineffective, as confirmed by the financial indicators of local budgets and scope of executed powers. The problems of formation of the reliable theoretical model of research were resolved by construction of related hypothesis using a benchmarking method and material analysis of foreign sources. Generally, the introduction of the model may lead to the GDP growth of the country due to provision of municipal services, improvement of the population quality of life that is the ultimate goal of each social state, as being Russia.